A new terraranan genus from the Brazilian Atlantic Forest with comments on the systematics of Brachycephaloidea (Amphibia: Anura) - Motta, Ana Paula [UNESP]; Goulart Taucce, Pedro Paulo [UNESP]; Baptista Haddad, Celio Fernando [UNESP]; Canedo, Clarissa (Wiley-Blackwell, 2021)
Eleutherodactylus bilineatus has long been an enigma. Recent phylogenetic analyses have recovered this species as part of a clade including Barycholos and Noblella, but the relationship among these groups still remains contentious. In this study, we test the phylogenetic position and reassess the taxonomic status of this long-term incertae sedis species. We use phylogenetic analyses of nuclear and mitochondrial gene sequences and data for external morphology and osteology of E. bilineatus and its related genera. We recover the species as an independent lineage forming a fully supported clade with Barycholos and Noblella. The combination of inferred relationships and morphological traits supports the erection of a new genus that we name and diagnose. Our analyses also recover a non-monophyletic Noblella and the species of the genus, although morphologically similar, are part of different clades: one including species from central Andes and the other one including species from northern Andes. Moreover, distribution patterns point out connections among distant biogeographical areas of South America and a widespread distribution of an ancestor for the clade including Barycholos, E. bilineatus, and Noblella. We also compare the relationships among clades of Brachycephaloidea and, hence, the family and subfamily classifications in different studies. We show that the family classification is probably far from becoming stable, mostly due to arbitrary selections of hierarchy of the clades. However, we show that by assigning a family to each of the highly supported and frequently recovered clades would render a more stable taxonomy of Brachycephaloidea.
Keywords: Barycholos; Eleutherodactylus bilineatus; Noblella; phylogeny; taxonomy